A Personalist Ontological Approach to Synthetic Biology. (8th December 2015) - Gómez‐Tatay, Lucía; Hernández‐Andreu, José Miguel; Aznar, Justo
Abstract: Although synthetic biology is a promising discipline, it also raises serious ethical questions that must be addressed in order to prevent unwanted consequences and to ensure that its progress leads toward the good of all. Questions arise about the role of this discipline in a possible redefinition of the concept of life and its creation. With regard to the products of synthetic biology, the moral status that they should be given as well as the ethically correct way to behave towards them are not clear. Moreover, risks that could result from a misuse of this technology or from an accidental release of synthetic organisms into the environment cannot be ignored; concerns about biosecurity and biosafety appear. Here we discuss these and other questions from a personalist ontological framework, which defends human life as an essential value and proposes a set of principles to ensure the safeguarding of this and other values that are based on it.